The Development of Coastal Village Communities through Village-Owned Enterprises (BUM Desa) in Pesawaran, Lampung - Chalida Syari; Hartoyo Hartoyo; Indra Gumay Febryano (JSW (Jurnal Sosiologi Walisongo), 2021)
Coastal village communities in Indonesia experience significant socio-economic disparities which make them more vulnerable as the marine ecosystem is badly affected by global warming. Concrete action needs to be conducted to resolve the problem better and do not make the coastal village communities poorer. This study aims to describe the empowerment program of coastal village communities through Village-Owned Enterprises (BUM Desa - Badan Usaha Milik Desa) in Gebang Village, Teluk Pandan Subdistrict and Durian Village, Padang Cermin Subdistrict, Pesawaran District, Lampung Province. Applying qualitative methods involved documentary study and in-depth interviews this research showed that in Gebang Village, there were empowerment efforts carried out by Mitra Bentala and CSR JAPFA Company Comfeed Indonesia Tbk as external supporting organizations. Inhibiting factors were the division of responsibilities and authorities among stakeholders who did not have a structure yet. Gebang Village used a participatory model, meanwhile, Durian Village combined endogenous (bottom-up) and community-based development models in their community empowerment. These findings proved the important roles of the authorities to form a more inclusive policy by involving internal and external stakeholders in order to accelerate the development of coastal village communities.__________The original draft of this article has been presented at the 6th International Conference on Social and Political Sciences (ICoSaPS) 2020, Strengthening Resilient Society in the Disruptive Era, Surakarta, October 7-8th, 2020.